Letter : Clothing for Spain - Conley, Andrew
028-0063-001 TELEGRAMS: AMALGAMATE, LEEDS TELEPHONE: LEEDS 20557. NATIONAL UNION OF TAILORS & GARMENT WORKERS Incorporating the Amalgamated Society of Tailors & Tailoresses, Scottish Operative Tailors & Tailoresses and the Garment Workers Union. HEAD OFFICE: Union Chambers. 20 PARK PLACE LEEDS, 1. General President: G. Rowlerson. General Secretary: A. CONLEY. 18th February 1937. Ref. 9/1/143. Mr. H. V. Tewson, Trades Union Congress General Council, Transport House, (South Block), Smith Square, LONDON, S.W.1. Dear Mr. Tewson, Clothing for Spain. Thanks for the information and advice conveyed in your letter of 16th February. We were becoming anxious about the action to be taken in arranging for the despatch of the clothing we have received. We are now clear and will act strictly in accordance with your directions, and everything will be in readiness for transport as soon as we receive your further advice. Yours sincerely, A. Conley. General Secretary. 292/946/28/63